The influence of COVID-19 on international labor migrations from Bosnia and Herzegovina to EU - Ćudić, Bojan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2020)
The article deals with the contemporary labor migrations from Bosnia and Herzegovina to Slovenia and the other countries of European Union, specifically during the period of the COVID-19 pandemic. On the basis of fieldwork among the participants in these migrations, it seeks to identify the specifics of circumstances and situations that arose suddenly with the closure of political borders and the demands of social distancing. In these circumstances, we supposed that labor migrants found themselves to be a particularly vulnerable group of population. The case study has denied that this is completely true. On the other hand, labor migrations from Bosnia and Herzegovina to Central, Western and North European and some non-European countries have been a continuous process for the last century and at least migration flows must be taken as a fact which directions, volumes and character are greatly influenced by labor market regulations in each individual EU member and other states. Periodically, specific political and social situations also gain importance. The COVID-19 pandemic has exactly such an impact.
Keywords: Bosna in Hercegovina; Bosnia and Herzegovina; COVID-19; delovne migracije; demogeografija; EU; Evropska unija; labor migrations; migracije; migrations; pandemije; population geography; Slovenia; Slovenija